INTEGRATING INTEGER PROGRAMMING WITH HEURISTIC ALGORITHM TO SOLVE THE WAREHOUSE RELOCATION PROBLEM OF AUTOMATED STORAGE AND RETRIEVAL SYSTEMS WITH MULTIPLE LOADING DEPOTS - Chang, Yung-Chia; Chang, Kuei-Hu; Meng, Hsien-Mi; Chang, Chih-Han (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The primary focus of the warehouse relocation problem is to systematically and efficiently move items already stored in the warehouse to newly planned storage locations, which is a critical issue for the successful operation of Automated Storage and Retrieval Systems (AS/RS). There is limited research on the warehouse relocation problem for AS/RS with multiple loading and unloading stations. To address this issue, this research proposed an approach to rearrange the materials stored in a unit-load AS/RS with multiple loading stations to a target assignment. A mathematical model based on integer programming was built to determine the optimal sequence for relocating storage locations and arrange the sequence of movement. Since this is at least NP-hard to solve, a heuristic algorithm was designed to solve this problem in several segments, enabling its application in practical scenarios with larger data scales to enhance the operational efficiency of automated storage systems. Computational experiments were conducted using various problem sizes to assess the performance of the proposed algorithm. Additionally, this study applied the proposed method to plan storage relocation for a large-scale automated AS/RS, which is operational at a computer hardware manufacturer in Taiwan, as a means to verify the feasibility and effectiveness of the method proposed in this research.